Regional income and wave energy deployment in Ireland - Niall Farrell; Cathal O'Donoghue; Karyn Morrissey (Papers in Regional Science, 2020)
Alongside environmental benefits, renewable energy deployment is often evaluated on grounds of regional development. Focusing on wave energy deployment in Ireland, this paper quantifies employment-related welfare change net of associated subsidy costs. Although the added employment reduces inter-regional inequality, certain subsidies increase total income inequality by a greater extent. Total inequality increases by 0.25% in the preferred scenario. This pattern of incidence persists under an optimistic scenario where all manufacturing activity is carried out locally. This finding highlights that policies of regional development should consider the spatial distribution of associated subsidy costs.
Keywords: 300; inequality; spatial microsimulation; regional development; renewable energy